PENGARUH JOB DESCRIPTION DAN TURNOVER INTENTION TERHADAP PRODUKTIVITAS KERJA KARYAWAN OPERASIONAL PRODUKSI PADA PT. BRAJA MUKTI CAKRA - Febriansyah, Ananda; Fadili, Dadan Ahmad (Politeknik Negeri Ambon, 2025)
Introduction: Productivity at PT. Several factors can influence Braja Mukti Cakra, including the job description and an employee's intention to stay with a company. A well-crafted job description can enhance the productivity of employees, and if you manage the process of people leaving the company effectively, it can also have a positive impact on overall productivity.Methods: The study uses a descriptive quantitative method. We obtained the data by distributing questionnaires to 147 operational employees. We used SPSS and Microsoft Excel to analyse this study, employing a technique known as path analysis.Results: A significant correlation exists between job descriptions and the intention to quit, with a correlation coefficient of -0.374, which is relatively weak. The impact of job descriptions on work productivity is pretty significant, with a value of 0.747, which is about 74.7%. The effect of turnover intention on work productivity is -0.123, which is about 12.3%. In essence, turnover intention negatively impacts productivity. The effect of the job description on how likely people are to want to leave their job, and how much work gets done, is 0.642, which is 64.2% on PT. Braja Mukti Cakra. The remaining 35.8% is attributed to other factors that were not examined in this research. Keywords: Job Description, Turnover Intention, Work Productivity